TEACHERS’ COMPETENCE IN THE DOMAIN OF LEARNING FACILITY BASED ON EDUCATION FOR SUSTAINABLE DEVELOPMENT - Mia Azzahra; Ghullam Hamdu (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
Teachers are an important component in determining the learning process in Education for Sustainable Development (ESD). The second report of the teacher education project for ESD Asia–Pasific held on 17th–19th September 2019 in Bangkok produced a competency framework for ESD teachers. This framework defines the competencies required by teachers to be involved in ESD which are implemented, developed, and evaluated by teacher education institutions. There are three domains in the teacher competency framework for ESD: facilitate learning, continue to learn and create, as well as connect, collaborate, and engage. However, this study only focused on one domain, which was learning facility. A total of 25 teachers from nine elementary schools provided their best answers based on the existing reality through a questionnaire distributed by the researchers about ESD-based teacher competence in the domain of the learning facility. This study aimed to determine the extent to which teachers understand and implement ESD-based competence in the domain of learning facilities in elementary schools. The data were processed with the Rasch model through the Winsteps application. The results of this study indicated that the teachers were able to implement it very well, but the idea was that the teachers still did not know that what they did led to ESD-based teachers' competence in the domain of learning facility.